Pengaruh Kepemimpinan, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai - Lestari, Ni Made Ani; Trarintya, Mirah Ayu Putri; Puja, I Made Suasti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the influence of leadership, work motivation, and work discipline on the performance of employees of the Taman Abiansemal Village Office in Badung. This research was conducted at the Taman Abiansemal Village Office in Badung with respondents being village office employees as many as 39 samples. So the method of determining the sample is the saturated sample method. The data collection methods used in this study are observation, interviews, literature studies, documentation and questionnaires. The data analysis techniques used were multiple linear regression analysis, determination coefficient analysis, t-test and F test. The results of the study were found that: 1) Partially, leadership has a positive and significant effect on employee performance at the Taman Village Office, Abiansemal, Badung Regency. 2) Partially, work motivation has a positive and significant effect on employee performance at the Taman Village Office, Abiansemal, Badung Regency. 3) Partially, work discipline has a positive and significant effect on employee performance at the Taman Village Office, Abiansemal, Badung Regency. 4) Simultaneously leadership, work motivation and work discipline have a positive and significant effect on employee performance at the Taman Village Office, Abiansemal.